2020
DOI: 10.1177/0030222820934944
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Attitudes Toward Death Among Chinese College Students and the Implications for Death Education Courses

Abstract: This study aims to explore the attitudes of college-age students to determine how they approach the idea of death by using a questionnaire that explores five separate dimensions of attitudes and beliefs. We received 1,206 completed surveys and found evidence of a substantial gender difference in attitudes toward death. These differences remain after adjustment for differences between males and females in other correlates of death attitudes and are not a function of gender differences in the dimensionality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…All of the interviewees who participated in this study were female nurses, the predominant group in China's nursing workforce, yet previous study in China found that there exists a substantial gender difference concerning the attitudes toward death among college students. [17] The possible gender difference among nurses' attitudes toward death and dying warrants further research.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the interviewees who participated in this study were female nurses, the predominant group in China's nursing workforce, yet previous study in China found that there exists a substantial gender difference concerning the attitudes toward death among college students. [17] The possible gender difference among nurses' attitudes toward death and dying warrants further research.…”
Section: Limitationsmentioning
confidence: 99%
“…[15] Receiving death education before embarking on clinical practice is helpful for nursing interns to care for dying patients. [16] Yet in China, there is a lack of death education in general [17] and a lack of an appropriate death education curriculum for health professionals in particular. Palliative care education is limited and disparate, and even medical teachers hold an ambivalent attitude toward palliative care and its education.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have come to different findings about the influencing factors of attitudes towards death [ 15 , 44 ], and this is related to the unique cultural background of the research objects [ 45 ]. In Chinese culture, the study community-dwelling older adults’ attitudes towards death were influenced by the number of diseases, discussion about life and death, marital status, and average income per month.…”
Section: Discussionmentioning
confidence: 99%
“…Pre epidemic anxiety disorder prevalence was 9.8%, while in a survey on isolation times 27.5% of students reported high levels of anxiety on questioning and 22.4% reported severe distress [33,34]. Chinese people are more valuable the notion of life and death due to socio-cultural differences, most of whom are not ready to face a loved one's sudden death and worry about their lives [35,36,37], which leads to a near step aggravation of anxiety into a fear of the COVID-19, which is the manifestation of anxiety being sudden from unconscious layer to conscious layer [38,39,40].…”
Section: Traumatic Psychological Problems In the Aftermath Of The Pan...mentioning
confidence: 99%